THE QUALITY AND PROCESSING USEFULNESS OF CHOSEN POLISH CARROT CULTIVARS - Agnieszka Sękara; Andrzej Kalisz; Stanisław Cebula; Aneta Grabowska (Acta Scientiarum Polonorum: Hortorum Cultus, 2012)
Carrot is one of the most important vegetables in Poland. It is the best carotenoid source in a human diet. Carrot is consumed in large quantities, thanks to continuous supply of fresh and storage roots as well as wide choice of processed products on a food market. Also consumer demands increase with regard to carrot quality and biological value. Polish breeders offer new carrot cultivars for processing. The choice of cultivar is the important factor under human control that may be used to improve carrot quality. The experiment was carried out at the University of Agriculture in Krakow, Poland, in the years 2009 and 2010, with carrot cultivars (‘Askona F1’, ‘DZE II F1’, ‘Galicja F1’, ‘Karioka F1’, ‘Karotan’, ‘Rumba F1’, ‘Afro F1’, ‘Broker F1’, ‘Kongo F1’, ‘Korund F1’) to evaluate its morphological and chemical characteristics and processing usefulness. Root morphological features predisposed investigated cultivars to mechanical harvest and processing. Analyzed chemical characteristics allowed to point out genotypes of high biological value and low nitrates accumulation, such as ‘Karioka F1’. The source of frozen cube of the best quality were ‘Karioka F1’, ‘Rumba F1’, and ‘Askona F1’, because of the lowest centrifugal leakage value. ‘Karioka F1’ and ‘Korund F1’ showed the greatest capacity for drying, because of the highest value of rehydration ratio. This shows that the comparison of the cultivars is necessary when the decision about the raw material selected for processing should be made. The parameters characterizing the minimally processed carrot cube quality were also correlated with morphological and chemical features of the roots. The equations allowing to predict the processing indices as the function of independent morphological and chemical variables were proposed with a use of the multiply regression method.